Pedagogia da presença: uma estratégia para o sucesso escolar - Santos, Maria de Fátima (2016)
The pedagogy of presence is used in reference schools in high school - EREM, the state of Pernambuco, as a management strategy to ensure the permanence and promote the academic success of students. Having as theoretical base the pedagogy of presence, the aim of this study was to analyze the educational experience of high school in Reference School Odorico Melo - EREM in the municipality of Parnamirim, Pernambuco state. It is intended to verify the contribution of this pedagogy to reduce dropout and academic achievement of students. For both a theoretical review of comprehensive education, interdimensional and truancy was held, as well as analysis of legal documents on the subject. This is a qualitative investigation of the case study type as a means of analyzing the procedures adopted by the school for the stay and the success of students in various fields of knowledge. We used the interview with teachers and managers of that school as a data collection instrument. Data analysis indicated that the pedagogy of presence has contributed rather to favor the permanence and success of the student and the school in which the teaching process takes care to use pedagogical practices that value the individual in its various dimensions, is pleasant and has guaranteed the success of the students. With this research, it is expected to contribute to other educational institutions can evaluate their teaching practices and strategies that promote improvement in school performance, especially in relation to the permanence and school success.